Mixing rich and asynchronous communication for new service development performance. (3rd March 2014) - Storey, Chris; Perks, Helen
<x xml:space="preserve">Abstract</x> This article explores the nature of relationships between internal communication modes, new service development (NSD) competencies (specifically learning and development competencies) and NSD performance. To do so, it draws on and advances communication theory by comparing and contrasting the contingent approach, favoured by media richness theory and media synchronicity theory, with the multiplicative manner of dual coding theory. Antecedent roles of rich and asynchronous communication modes for two NSD competencies are investigated, and their function as critical contingency variables affecting the competencies–performance link is unravelled. An empirical quantitative study of senior managers of leading service firms was conducted, with a survey‐based methodology. Results show that a learning competency drives development competency which in turn drives NSD performance. Asynchronous communication is essential for learning competency but not for development competency. In contrast, rich communication underpins development but has no direct effect on learning competency. Rich communication is essential for NSD performance when a firm has a low development competency. The interaction between asynchronous and rich communication is shown to be positive for learning, whereas surprisingly it is negative for development competency.